2013
DOI: 10.1371/journal.pone.0067281
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Estimating Dose Responses for Polymer Gels Using Texture Analysis of Scanning Electron Microscopy Images

Abstract: Polymer gels are regarded as a potential dosimeter for independent validation of absorbed doses in clinical radiotherapy. Several imaging modalities have been used to convert radiation-induced polymerization to absorbed doses from a macro-scale viewpoint. This study developed a novel dose conversion mechanism by texture analysis of scanning electron microscopy (SEM) images. The modified N-isopropyl-acrylamide (NIPAM) gels were prepared under normoxic conditions, and were administered radiation doses from 5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The low-toxicity N -isopropylacrylamide (NIPAM) polymer gel dosimeter proposed by Senden et al [ 1 ] has been intensively researched for the optimization of its formula [ 2 ] and its readout systems. The results showed that the NIPAM gel dosimeter had a high linear dose response ranging from 2–15 Gy [ 3 ], and can be read out by various scanning tools [ 4 , 5 ]. During gel reading, the changes of proton groups in gels can be measured using magnetic resonance imaging (MRI), and the T2 results can be correlated with the 3D dose distribution [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low-toxicity N -isopropylacrylamide (NIPAM) polymer gel dosimeter proposed by Senden et al [ 1 ] has been intensively researched for the optimization of its formula [ 2 ] and its readout systems. The results showed that the NIPAM gel dosimeter had a high linear dose response ranging from 2–15 Gy [ 3 ], and can be read out by various scanning tools [ 4 , 5 ]. During gel reading, the changes of proton groups in gels can be measured using magnetic resonance imaging (MRI), and the T2 results can be correlated with the 3D dose distribution [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entropy values were calculated from different random sections of the micrographs (71x71 pixels), and this parameter allowed evaluating the homogeneity of the particle phases (Shih et al 2013).…”
Section: Characterizationmentioning
confidence: 99%
“…Borehole-wall images can be classified into different categories based on their texture similarity [ 14 ]. Gray level co-occurrence matrix (GLCM) is probably the most popular method for texture analysis [ 15 ]. However, due to the similarity of horizontal crack images and intact rock mass images, a single statistical method of extracting the texture feature may not be sufficient for the classification task.…”
Section: Introductionmentioning
confidence: 99%